Penerapan Model Pembelajaran Kooperatif dengan Integrasi Teknologi dalm Meningkatkan Hasil Belajar Peserta Didik SMP Negeri 1 Mataram - Dwiantari, Baiq Fany Rindang; Baidowi, Baidowi; Suntoko, M. Iwan (FKIP Universitas Mataram, 2024)
This research aims to improve the learning outcomes of eighth-grade students in class VIII-H by implementing a cooperative learning model integrated with technology. This is a classroom action research that conducted in 3 cycles, focusing on improving student learning outcomes. The data collection techniques were obtained through tests and observations. The research findings indicate improved mathematics learning outcomes of VIII-H students at SMPN 1 Mataram following the implementation of a cooperative model with technology integration. The improvement is clear from the average scores recorded in each cycle. In the first cycle, the average score was 63.29, with a classical completeness rate of 44.74%. In the second cycle, the average score increased to 71.97, and the classical completeness rose to 73.68%. By the third cycle, the average score further improved to 84.61, resulting in a classical completeness of 84.21%. This improvement can be attributed to the student's success in completing the tests given during the learning process, which was enhanced by integrating technology in the form of PowerPoint, Geogebra, and Quizizz. The results of this study conclude that the cooperative model with technology integration can enhance students' mathematics learning outcomes